Second harmonic generation in the Weyl semimetal TaAs from a quantum kinetic equation - Li, Zhi (2018)
We classify the sources of second harmonic generation (SHG) of the Weyl semimetal TaAs by collisionless quantum kinetic equation into three kinds: i.e., injection current from the canonical band dispersion, shift current from a gauge invariant shift vector, and anomalous current from Berry curvature associated with the Fermi surface. Importantly, by using the realistic band model for TaAs, we predict that the SHG in TaAs is predominately contributed by the shift current, while the anomalous current has a minute contribution when the Weyl point is exactly located on the Fermi surface. Moreover, we highlight that the SHG contributed by the anomalous current decays fast with the increasing frequency of incident photons, and could be enhanced by proper electron or hole doping of TaAs.